Body-temperature programmable thermoplastic elastic shape memory polymers - Tan, Jason Jia Jun (Nanyang Technological University, 2021)
Shape memory materials (SMMs) are a special type of material where, after being severely and quasi-plastically deformed, in the presence of the right stimulus, are able to recover their original shapes. Shape memory polymer (SMP), in particular, is an interesting material as it has low production cost, large elastic deformation and biodegradability which are highly sought after in the garment industry. Nowadays consumers are seeking for better comfort and functionality in their footwear, making these characteristics highly ranked during footwear fabrications. Many methods were created to provide better comfort fitting, such as 3D printing, however 3D printing can be a costly process. Therefore, SMPs were introduced as the cheaper solution for comfort fitting. This project is a comparative theoretical investigation on the shape memory effect in body-temperature programmable thermoplastic elastic shape memory polymers. Such polymers have yet been achieved, as currently, there are either body-temperature programmable thermoset SMP or SMP that is not programmable at body-temperature. Therefore, in this project, a new series of SMP mixtures containing thermoplastic rubber (TPR) and polylactic acid (PLA), and thermoplastic rubber (TPR) and thermoplastic polyurethane (TPU), were mixed together at different volume percentages and their thermo-responsive shape memory effect were being investigated. Various experimental methods were conducted to examine the fabricated SMP mixtures for their shape memory behaviours. The methods include, scanning electron microscope (SEM), cyclic tensile test (CTT), and finding the shape recovery ratio and shape fixity ratio. Results shows that all fabricated SMP mixtures possesses great shape recovery, while the shape fixity greatly depends on the volume percentage of TPR in the SMP mixtures. With great elasticity and stretchability, the SMP mixtures are perfect for comfort fitting applications.